Pendampingan Akreditasi Kampus Berbasis Outcome-Based Education (OBE) dan Digitalisasi Mutu di PTKIS (Sekolah Tinggi Ilmu Tarbiyah) Tanggamus Provinsi Lampung - Siti Patimah; A. Gani; Fahrina Yustiasari Liriwati; Abdul Latief Arung Arafah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Private Islamic Religious Colleges (PTKIS) play a strategic role in developing superior human resources with Islamic character. However, in practice, many PTKIS face challenges in meeting higher education quality standards and achieving optimal accreditation. Accreditation assistance based on Outcome-Based Education (OBE) and quality digitization are innovative solutions to improve the effectiveness of education quality management. OBE emphasizes the importance of learning outcomes integrated into the curriculum, learning process, and assessments that are measurable and relevant to the needs of the workplace. Meanwhile, quality digitization supports the efficient, transparent, and real-time management of academic data, forms, and accreditation reporting. Through the integration of these two approaches, PTKIS can improve accountability, accelerate the accreditation process, and ensure the achievement of sustainable quality standards. This article discusses the strategy of OBE-based accreditation assistance and quality digitization at the Tanggamus Islamic Education College, Lampung Province, highlighting the implementation process, obstacles encountered, and solution steps that can be applied to strengthen the PTKIS's internal quality assurance system.